Phytochemical Screening and Antimicrobial Activity of Entandrophragma angolense - Anthonia Ogheneruno Ugboduma; Francis Adu; Christian Agyare; Kofi Annan; Samuel Osei-Asante (Journal of Pharmacy and Nutrition Sciences, 2013)
Entandrophragma angolense (Welw.) C.DC. (Meliaceae) is a deciduous plant commonly found on in west Africa and it is used for treatment microbial infections, wounds, rheumatic and arthritic pains. The methanol stem bark extract was investigated for its antimicrobial activity using the agar well diffusion method and macro-dilution technique and time kill kinetics. The antimicrobial activity of the methanol extract and its fractions were evaluated against five bacteria species and a fungus including Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212, Bacillus subtilis NCTC 10073, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 4853 and clinical strains of Candida albicans and some of the test bacteria. Phytochemical screening of the crude extract revealed the presence of tannins, flavonoids, alkaloids, terpenoids, saponins and cardiac glycosides. The MICs of the methanol extract against the test organisms were: S. aureus (11.0 mg/mL), E. faecalis (9.0 mg/mL), B. subtilis (13.0 mg/mL) E. coli (17.0 mg/mL), P. aeruginosa (19 mg/mL) and C. albicans (15.0 mg/mL). The fractions of the methanol extract (pet ether, ethyl acetate and aqueous fractions) exhibited varying antimicrobial activities, with the highest activity exhibited by the aqueous fraction. The extract exhibited bacteriostatic and fungistatic activity against all test organisms. Time kill studies showed that the extract exhibited an inhibition of bacterial and fungal growth. The results indicate that the methanol stem bark of E. angolense has antibacterial and antifungal activities and may justify the medicinal uses of the plant in the management of bacterial and fungal infections.